FARMERS' PARTICIPATION IN THE IMPLEMENTATION OF THE PEOPLE'S OIL PALM REJUVENATION PROGRAM (PSR) IN TELUK PANJI VILLAGE, KAMPUNG RAKYAT DISTRICT, SOUTH LABUHANBATU REGENCY - Ardila; Tuty Ningsih (RADJA PUBLIKA, 2026)
The Small-Scale Oil Palm Replanting (PSR) Program is a government effort to increase the productivity of small-scale oil palm plantations by replanting unproductive plants. This study aims to determine the level of farmer participation in the PSR program and analyze the relationship between participation factors and farmer participation in Teluk Panji I Village, Kampung Rakyat District, South Labuhanbatu Regency. This study uses a quantitative descriptive method, with 46 farmers participating in the PSR program as respondents. Data analysis was carried out using a Likert scale and Spearman Rank Correlation test with the help of IBM SPSS Statistics Version 22. The results showed that the level of farmer participation in the PSR program was relatively high, namely 79.8%. Based on the results of the Spearman Rank correlation test for four internal factors, two variables showed a significant relationship with farmer participation: motivation (rs = 0.577; sig. = 0.000) and education level (rs = 0.308; sig. = 0.037). Meanwhile, the other two variables were not significant: income (rs = 0.187; sig. = 0.212) and farming experience (rs = 0.257; sig. = 0.084). Then, two external factors showed a significant relationship with farmer participation: the availability of production facilities (rs = 0.621; strong category) and capital assistance (rs = 0.439; moderate category). The PSR program in Teluk Panji I Village was quite successful, as evidenced by the high enthusiasm of farmers to participate in the program.